Chronic Heart Failure and Cytokines - Adizova Dilnavoz Rizokulovna (Researchparks Publishing, 2022)
Chronic heart failure (CHF) is considered as a global non-communicable pandemic. In the pathogenesis of CHF, many factors are considered, including inflammatory cytokines. Cytokines is a group of soluble peptide mediators of the immune system, which is necessary for its development, functioning and interaction with other body systems. TGF-β1 is a member of the group of multifocal cytokines. Many studies have shown the roles of TGF-β1 activation in the development of CVD, such as hypertension, cardiac hypertrophy and cardiac fibrosis leading to heart failure, as well as restenosis after coronary intervention and atherosclerosis. An analysis of the results of the studies performed indicates the direct involvement of TGF-β1 and its genetic structure in the processes of myocardial remodeling in heart failure, and also substantiates the need for further research in this direction.